PENGARUH GOOD GOVERNANCE, KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN (Studi Empiris Pada SKPD Kota Dumai) - Tua, Manuppan Bangun; Taufik, Taufeni; Haryani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aim of this research is to to analyze the effect of good governance, human resource competency and internal control system toward information quality of local government financial statement. The population of this research chief financial subsections and financial staff that work on the unit of Work in Dumai city. The sampling technique using purpose sampling. Total repondent in this research are 64 respondent. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The result of this study indicates that good governance, human resource competency and internal control system has influence to information quality of local government financial statement. Based on the calculation of the coefficient of determination (Adjusted RÂ²) obtained a value of 0,771. This shows that the influence of the independent variables in the dependent 77,1% and the remaining 22,9% influenced by other variables.Keywords: Local Government Financial Statement Quality, Information Value, Good Governance, Competency, Internal Control.